2017
DOI: 10.1016/j.jplph.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Variation in relative water content, proline accumulation and stress gene expression in two cowpea landraces under drought

Abstract: Many landraces of cowpea [Vigna unguiculata (L.) Walp.] are adapted to particular geographical and climatic conditions. Here we describe two landraces grown respectively in arid and temperate areas of Algeria and assess their physiological and molecular responses to drought stress. As expected, when deprived of water cowpea plants lose water over time with a gradual reduction in transpiration rate. The landraces differed in their relative water content (RWC) and whole plant transpiration rate. The landrace fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 67 publications
6
45
0
2
Order By: Relevance
“…In our study significantly higher proline content was recorded in onion variety Bhima Kiran that might protect the cellular membrane and the various metabolic processes associated with it under water deficit condition (Table 2). A recent finding in cowpea by Zegaoui et al, (2017) supports the present result in onion crop under drought stress.…”
Section: Physiological and Biochemical Traitssupporting
confidence: 90%
“…In our study significantly higher proline content was recorded in onion variety Bhima Kiran that might protect the cellular membrane and the various metabolic processes associated with it under water deficit condition (Table 2). A recent finding in cowpea by Zegaoui et al, (2017) supports the present result in onion crop under drought stress.…”
Section: Physiological and Biochemical Traitssupporting
confidence: 90%
“…Meanwhile, water stress increased D in order to counteract the inadequate water status, as indicated by the lower RWC. Several studies have also shown a decrease in RWC with increasing water stress (Boughalleb and Hajlaoui 2011;Ghahfarokhi et al 2015;Zegaoui et al 2017). Water stress can increase D since reductions in turgor pressure and cell expansion result in the same dry mass within a smaller leaf area (Peña-Rojas et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Since stem diameter shrinkage indicators such as the maximum daily shrinkage, daily stem diameter increment, and daily stem diameter variation cannot reflect sap flow at a half-hour time resolution, TWD is considered a better choice for indicating sap flow when the time scale required is less than 1 day. Transpiration can cause variations in plant moisture indices, including plant moisture content [34,35], water potential [36], and stem sap flow [37,38]. It would be good to acknowledge that coupled TWD and actual tree water content, for example, using time domain reflectometry probes or frequency domain reflectometry probes [39], should be analyzed to confirm whether TWD is a good tree moisture indicator.…”
Section: Discussionmentioning
confidence: 99%